Studies on Some Heavy Metals Removal inIndustrial and Drinking Water: A review - Msahir Ateshan, HAIDER (University of Thi-Qar Journal of Science, 2025)
In order to learn many new concepts and details in our field of study, we analyzed and investigated a number of prior studies in this work. The majority of these studies were conducted within the last five years, and they covered techniques for removing heavy metals from aqueous media by measuring various physical and chemical properties like initial concentration pH, and how these properties affect heavy metals in this study, we used heavy metals like Copper, Zinc, and Lead. Zn = 80.7% in sewage water, Cu = 97.10% in drinking water, and lead (Pb) = 100% in industrial medium. Natural zeolite was the most effective adsorbent material utilized in the removal procedure, along with silica and live bacteria. Adsorbents are used to remove heavy metals from aquatic media. The effectiveness of these materials in removing these heavy metals from polluted water has been confirmed. This removal is done according to certain conditions, such as pH, temperature, etc., and the removal efficiency varies from one metal to another. This is what we will confirm in this chapter by discussing various references and modern scientific articles in which heavy metals were investigated from polluted water using different adsorbent materials.